Ursachen und Management von IOL-Dislokationen = Aetiology and management of IOL dislocations - Khoramnia, Ramin; Baur, Isabella; Auffarth, Gerd U. (Klinische Monatsblätter für Augenheilkunde, 2023)
Early (< 3 months) intraocular lens (IOL) dislocation occurs due to insufficient fixation in the capsular bag, while late dislocation (≥ 3 months) is due to increasing insufficiency of the zonular apparatus. Iris-fixated IOL (IFIOL) and suture- or sutureless-fixated scleral IOL (SFIOL) are currently the most commonly used methods when IOL exchange is indicated. Different methods of scleral fixation with or without sutures have been described. The most important techniques are summarised in this paper. IFIOL and SFIOL allow comparable visual outcomes but differ in their risk profile. The decision of which method to use should be made case by case and in accordance with the surgeon's preference.
Gesehen am 08.09.2023
Artikel online veröffentlicht: 12. Juli 2023